2018
DOI: 10.1007/s41547-018-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of enamel surface roughness after different adhesive removal techniques for orthodontic bracket debonding

Abstract: Background The objectives of this study were to explore traditional resin removal procedures in the debonding process and evaluate the Er:YAG laser as a plausible option. Methods Sixty premolar teeth were bonded with brackets. Then, brackets were removed and five adhesive clean-up methods were tested against control teeth: (a) Er:YAG laser at 200 mJ and 20 Hz; (b) Er:YAG laser at 305 mJ and 10 Hz; (c) 20-fluted flame-shaped tungsten carbide bur at high-speed; (d) #8-fluted round tungsten carbide bur at low-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…In the present study, two types of tungsten carbide burs have been applied: a 12-fluted round end tapered fissure tungsten carbide bur and a 12-fluted round tungsten carbide bur with reduced vibrations. As it had been assumed based on the study by Palmer et al [22], the visual assessment confirmed more enamel damage caused by a round bur. However, using the SEM image evaluation in their study, Pignatta et al [9] concluded that a tungsten carbide bur caused several scratches on the enamel surface, which were not observable after polishing.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…In the present study, two types of tungsten carbide burs have been applied: a 12-fluted round end tapered fissure tungsten carbide bur and a 12-fluted round tungsten carbide bur with reduced vibrations. As it had been assumed based on the study by Palmer et al [22], the visual assessment confirmed more enamel damage caused by a round bur. However, using the SEM image evaluation in their study, Pignatta et al [9] concluded that a tungsten carbide bur caused several scratches on the enamel surface, which were not observable after polishing.…”
Section: Discussionsupporting
confidence: 63%
“…After they had been rinsed with water for 30 seconds and air dried to frosty-white appearance, the buccal surfaces of the teeth were treated with the Aspire primer 7GM (OC Orthodontics) and light-cured for 10 seconds with a LED curing unit (Woodpecker, Guilin, China). Mesh pads of metal brackets Ortho Organizer Elite OptiMIM (Henry Schein® Orthodontics, Carlsbad, CA, USA) were removed by a dull round end tapered multifluted tungsten carbide bur at high speed to determine the mode of bond failure at the bracket base-adhesive interface, allowing the complete amount of resin to be left on the enamel surface of all 210 teeth [22]. A small amount of Aspire resin 5GM (OC Orthodontics) was put on the bases of metal brackets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 One investigator conducted all experiments to remove variability between operator techniques. 6 The tooth was embedded in a rectangular mold (about 25 mm width and 35 mm length) longitudinally which, is filled with stone only the buccal surface of the crown was seen (Figure 1). Thirty-five teeth were examined using a profilometer device to assess whether the teeth have already roughness or not, five teeth were excluded and, 30 teeth were involved in the study according to the inclusion criteria of the study.…”
Section: Methodsmentioning
confidence: 99%